PENGUMPULAN DAN PENYAJIAN DATA (Teknik Pengumpulan, Penyajian dan Analisis Data) - Riswan; Zamsiswaya (STKIP Subang, 2026)
Qualitative research requires systematic data management to produce valid and scientifically accountable findings. This article aims to examine the concepts, techniques, and procedures of data collection, data presentation, and data analysis in qualitative research. The study employs a literature review method by analyzing various scholarly sources related to qualitative research methodology. The findings indicate that data collection is conducted through observation, interviews, documentation, and triangulation, which function to obtain in-depth information while ensuring data credibility. Data presentation is the process of organizing and displaying data in the form of narratives, tables, graphs, or matrices to facilitate understanding and analysis. Meanwhile, data analysis is carried out through the stages of data collection, data reduction, data display, and conclusion drawing and verification in a continuous and interactive manner. Data trustworthiness in qualitative research can be enhanced through triangulation, prolonged engagement, persistent observation, member checking, and audit trails. Therefore, the success of qualitative research largely depends on the appropriateness of data collection techniques, the systematic presentation of data, and the rigor of data analysis, resulting in credible, accurate, and meaningful findings that contribute to the advancement of knowledge.